Cheese Fruit Salad Making Training as an Economic Business Program for Lower-Middle Class Communities - Rachmawati, Diya; Ghofur, Abdul; Badriyah, Nurul; Titin (Proceeding of International Management Conference and Progressive Papers, 2025)
In a marketing, there are many forms and various kinds of food from small to large and from cheap to expensive. Today’s society tries to consume healthy food, it must become a habit so that the body’s health is maintained. This is done by choosing natural foods and in fresh conditions, without preservatives. One of the healthy foods that are safe for consumption are salads, either vegetable or fruit salads. Fruit salad is a healthy alternative. It can even prevent and treat several types of diseases. Vegetables and fruit in salads are rich in nutrients, nutritional content, contain high fiber, also contain various vitamins and minerals that are very useful for body health. We often do not realize, a small bowl of fruit salad with the right composition, will be very useful for the ’freshness’ of our body. Salad provides the body with so much fiber which in turn lowers cholesterol and reduces constipation. In line with the problems found, this service provides more of a teaching on how to use fruits to be processed into salads which can later be developed to increase the economy of the community through sales by utilizing e-commerce, but little knowledge is owned by the lower middle class. The teaching pattern is by providing recipes and field practice of making various kinds of vegetable salads and mixing them with other ingredients such as fruit and seeds, as well as knowing the types of packaging and how to pack them well and then marketing them through e-commerce. It is hoped that the middle and lower people will understand more about how to process salads to be durable and can open up opportunities to pursue the healthy food business.